Long Non-coding RNA TDRKH-AS1 Promotes Colorectal Cancer Cell Proliferation and Invasion Through the β-Catenin Activated Wnt Signaling Pathway - Jiao, Yang; Zhou, Jialiang; Jin, Yecheng; Yang, Yingxin; Song, Mingxu; Zhang, Ling; Zhou, Jiayan; Zhang, Jiwei (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is a common cancer with a lower five-year survival rate in the worldwide. Recently, long noncoding RNAs (lncRNAs) have been well-studied as the oncogenes or the tumor suppressors in multiple malignancies, including CRC. However, their biological functions and potential mechanisms in human cancer remain unclear. Here, we evaluated the expression of TDRKH-AS1 in CRC tissues and identified its potential targets. We found that TDRKH-AS1 is upregulated in majority CRC patients, which is also significantly correlated with their malignant characteristics and their dismal prognoses. The high expression of TDRKH-AS1 can promote cancer cell proliferation substantially and invasion based on in vitro experiments. We also recognized that the TDRKH-AS1 targets the β-catenin in the Wnt signaling pathway to exert its carcinogenic activity. TDRKH-AS1 could serve as a promising prognostic predictor and a potential therapeutic target for further early diagnoses and treatments via a non-invasive method.